2011
DOI: 10.1007/s00384-011-1328-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous interferential electrical stimulation for management of neurogenic bowel dysfunction in children with myelomeningocele

Abstract: This pilot study showed that IF therapy is safe, noninvasive, and effective modality to improve constipation symptoms and anorectal manometry parameters in children with history of myelomeningocele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 20 publications
1
50
0
Order By: Relevance
“…Moreover, a study by Kajbafzadeh et al [6] who reported that, Although IF electrical stimulation did not apply on pelvic floor muscles directly, modulation of sacral reflexes occurs improving the bowel control after using IF stimulation technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a study by Kajbafzadeh et al [6] who reported that, Although IF electrical stimulation did not apply on pelvic floor muscles directly, modulation of sacral reflexes occurs improving the bowel control after using IF stimulation technique.…”
Section: Discussionmentioning
confidence: 99%
“…Deep electrical stimulation by using interferential current stimulates the skin nerve fibers which can lead to facilitation of the parasympathetic nerve fibers and modulate the sacral reflexes controlling the bowel movment [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This is difficult to accomplish as sham stimulation so far has been applied via no current passing between electrodes with the participant being told that the current is subsensory. 23,38 This may convince children, but is less likely to do so in adults. These studies also required participants to come in to the clinic for treatment, which also makes it easier for an investigator to create a realistic sham scenario, whereas more recent devices are small enough for patients to take home and use.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty Iranian children with neuronal bowel dysfunction from myelomeningocele participated in a randomized controlled trial. 38 Constipation, as determined by stool form, decreased and the neurogenic bowel dysfunction scores improved from 'moderate' to 'mild' in the interferential current therapy group. These results were noted at 6 months after receiving treatment with an overall improvement in 73% of the children in the interferential current therapy group.…”
mentioning
confidence: 89%
See 1 more Smart Citation